Salesforce platform app builder certification training. (Packt Publishing, 2022)
Prepare yourself for the Salesforce Platform App Builder Certification Exam by taking this course. About This Video Design data model, user interface, business logic, and security for custom applications Customize application for mobile use Design reports and dashboards In Detail The Salesforce Platform App Builder Certification Training helps you explore everything from understanding basic Salesforce concepts to building apps on the platform, setting up security and access permissions, and creating workflow automation procedures. The course also prepares you for the Salesforce Platform App Builder Certification Exam. We will start by getting an in-depth understanding of the exam details and the requirements. Next, we will explore Salesforce and learn to create a Salesforce account. We will look at the process of customizing profile and role creation. We will also cover Salesforce data and how to create custom objects. We will explore the lightning console and understand how to move from classic to lightning. Along the course, we will learn data modeling and management, custom objects, and understand standard and custom objects. We will learn to demonstrate how to create various lightning pages and how to create a roll-up summary field. Learn about security access and grant access using hierarchies and about permission sets. Explore the various types of reports and create a custom report type, create joined reports and dashboards. By the end of this course, you will have understood the topics that will help you pass the certification exam. Audience This Salesforce Platform App Builder Certification course is suitable for individuals looking to build a career in Salesforce, app developers, system administrators, sales representatives, and product managers. Learners need to possess an undergraduate degree or a high school diploma.